2017
DOI: 10.1002/2016wr020084
|View full text |Cite
|
Sign up to set email alerts
|

Big Ship Data: Using vessel measurements to improve estimates of temperature and wind speed on the Great Lakes

Abstract: The sheer size of many water systems challenges the ability of in situ sensor networks to resolve spatiotemporal variability of hydrologic processes. New sources of vastly distributed and mobile measurements are, however, emerging to potentially fill these observational gaps. This paper poses the question: How can nontraditional measurements, such as those made by volunteer ship captains, be used to improve hydrometeorological estimates across large surface water systems? We answer this question through the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…GP have been used byFries et al to improve the accuracy of hydrological models[Fries and Kerkez 2017], and Troutman et al have used GP for identifying the contribution of wastewater flows in combined sewer systems[Troutman et al 2017]. …”
mentioning
confidence: 99%
“…GP have been used byFries et al to improve the accuracy of hydrological models[Fries and Kerkez 2017], and Troutman et al have used GP for identifying the contribution of wastewater flows in combined sewer systems[Troutman et al 2017]. …”
mentioning
confidence: 99%
“…This paper seeks to fill this gap. Our work echoes and draws from recent studies such as Fries and Kerkez (2017) and Mazzoleni et al (2015Mazzoleni et al ( , 2017Mazzoleni et al ( , 2018 on merging crowdsourced data with existing environmental monitoring or modeling data.…”
Section: Introductionmentioning
confidence: 73%
“…Crowdsourcing in our study context is the obtaining of data through public sensors, social media, and the Internet of Things (e.g., smartphones, cameras, traffic lights, and moving cars). It has the ability to provide high spatio-temporal resolution data efficiently and economically and, hence, offers immense potential for addressing the problem of data availability in related areas of research and management as has been demonstrated by a number of studies (Fries & Kerkez, 2017;Rabiei et al, 2013;Yang & Ng, 2017). In recent years, crowdsourcing has been applied in many areas, including meteorology (Overeem et al, 2016), hydrology (Mazzoleni et al, 2015(Mazzoleni et al, , 2017, environment (Breuer et al, 2015;Zheng et al, 2017), and geography (Su et al, 2017;Zook, 2017).…”
Section: Introductionmentioning
confidence: 99%